Influence of Content Marketing, E-WOM, and Product Quality on Repurchase Intention (Study of Generation Z Who Buy COSRX Skincare on the TikTok Platform in Surabaya City) - Oktaviana Nawang Ardi; Budi Prabowo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research is based on the emergence of various types of skincare that are being discussed by Gen Z regarding products or skincare originating from South Korea on the TikTok platform. The main purpose of this study is to examine and further analyze content marketing, E-WOM, and product quality on the repurchase intention of COSRX skincare products in Surabaya City. This study involved 100 samples of respondents who had bought and used COSRX skincare from Gen Z in Surabaya City. The method used is a quantitative approach with a non-probability sampling technique through purposive sampling and primary data analysis. The analysis technique uses multiple linear regression analysis and data processing using the SPSS 25 program. The results obtained show that the F test produces an F-count of 99.290 > ftable 270 with a sign value. 0.00 <0.05, then H1 is accepted. The t-test in content marketing produces a tcount of 5.964> t table 1.985, for E-WOM produces a tcount of 3.367> t table 1.985, and product quality produces a tcount of 2.538> t table 1.985. So, the results of the T-test H2, H3, and H4 are accepted. Based on these results, it can be concluded that content marketing, E-WOM, and product quality simultaneously have a significant effect on repurchase intention. Partially, content marketing, E-WOM, and product quality have a significant effect on repurchase intention.